Synthesis and characterization of monomeric and polymeric Pd(II) and Pt(II) complexes of 3,4-ethylenedioxythiophene-functionalized phosphine ligands - Velauthamurty, K.; Higgins, S.; Rajapakse, R.M.G.; Bacsa, J.; Zalinge, H.; Nichols, R.J.; Haiss, W. (Royal Society of Chemistry, 2009)
Phosphine ligands bearing 3,4-ethylenedioxythiophene (EDOT) groups, in which a Ph2P group is either connected directly to the thiophene ring [Ph2P(5–EDOT), 1] or to the EDOT ethylenebridge via a methylene (4) or longer (7) ‘spacer’, have been prepared, together with their complexes cis-[MCl2(L)2] (M = Pd and Pt). The electrochemical co-polymerization of the complexes with EDOT was investigated, with a view to making conducting polymersincorporating covalently-bound metal–phosphine complexes. Although polymer-coated electrodes were obtained in all experiments, XPS measurements established that polymersmade in the presence of cis-[MCl2(1)2] consisted only of poly(3,4-ethylenedioxythiophene) (PEDOT), whereas polymers made in the presence of cis-[MCl2(L)2] (L = 4, 7) were genuine co-polymers containing Pd(II) or Pt(II) complexes.